Trypsin and aminopeptidase activities in blood-fed females Anopheles dirus (diptera: culicidae) of differing susceptibility to Plasmodium yoelii nigeriensis - Somboon P. (2014)
Midgut proteolytic enzymes contribute to the success or failure of Plasmodium infection of the mosquito. The present study investigated trypsin and aminopeptidase activities in the midgut of two strains of Anopheles dirus selected for susceptibility and refractoriness to Plasmodium yoelii nigeriensis. At intervals of 6 hours following a bloodmeal, the midguts of fully engorged female mosquitos were dissected, homogenized, and assayed for enzyme activity. No differences trypsin activity (nmole/min) were observed between the two strains throughout the course of blood digestion. By contrast, the aminopeptidase activity measured at 0 to 18 hours post-feeding was the same for the two strains, but at 24, 30 and 36 hours significantly less activity was observed in the refractory females. The results suggest neither trypsin nor aminopeptidase plays a role in the limitation of parasite development.